Intranasal administration of stem cell derivatives for the treatment of AD animal models: a systematic review and meta-analysis - Hua, Zilin; Zhou, Nan; Zhou, Zijing; Fu, Zewei; Guo, Ruiyun; Akogo, Herman Yao; Yang, Jiayin; Yu, Meixuan; Jiang, Yujie; Lan, Siyi; Chang, Haixia; Ma, Jun; et al. (Stem cell research & therapy, 2025)
Background Alzheimer's disease (AD) is a neurodegenerative disorder with increasing prevalence and limited efficacy of current therapies. Stem cell-derived therapies have attracted attention for their potential neurodegenerative and reparative effects. Intranasal administration provides a non-invasive route that bypasses the blood-brain barrier and delivers stem cell derivatives directly to the brain. Although studies have shown that the intranasal administration of stem cell derivatives alleviates symptoms in animal models of AD, a comprehensive meta-analysis evaluating their therapeutic efficacy is yet to be conducted. This study aims to evaluate the efficacy of intranasal stem cell derivatives therapies in AD animal models and provide a foundation for clinical translation. Methods We conducted a systematic literature search across four databases (Pubmed, Embase, Web of Science and Cochrane Library) using subject terms and complementary keywords. After applying inclusion and exclusion criteria, data were extracted using Origin 2024 software and analysed using Review Mange 5.4. The SYRCLE tool was applied to assess study quality and evaluate the potential risk of bias systematically. Results This meta-analysis of 14 studies investigated the efficacy of intranasal stem cell-derived therapies in animal models of Alzheimer's disease (AD). Using predominantly mouse and rat models from diverse geographical locations and employing various stem cell types (bone marrow, umbilical cord blood, adipose tissue, hiPSCs), the analysis revealed a significant reduction in amyloid-beta (A[beta]) deposition (SMD = -2.69, p < 0.0001). Subgroup analyses indicated that stem cell source, stem cell derivative types and A[beta] detection method were not primary drivers of heterogeneity. Furthermore, treatment significantly reduced inflammatory markers IL-1[beta] (SMD = -0.92, p = 0.008) and IBA-1 (SMD = -1.68, p = 0.006), suggesting an anti-inflammatory effect. Auxiliary outcomes CD68 and GFAP also exhibited decreased expression levels. Improved cognitive function was evident, as measured by increased target quadrant dwell time (MD = 10.17, p < 0.00001) and decreased escape latency (MD = -15.74, p = 0.003) in behavioral experiments, and enhanced recognition in the Novel Object Recognition Test (NORT) (SMD = 1.10, p = 0.006). Nissl staining demonstrated a significant reduction in neuronal cell death (SMD=-3.33,p < 0.00001),suggesting a role in neuronal repair.Together, these findings support the potential of intranasal stem cell-derived therapies to improve Alzheimer's disease pathology, neuronal repair, and cognition in animal models. Conclusion Intranasal administration of stem cell derivatives has demonstrated efficacy in Alzheimer's disease (AD) animal models, leading to reductions in amyloid-beta (A[beta]) deposition, cognitive improvement, repair neurons and attenuation of inflammatory responses. However, limitations such as potential publication bias and heterogeneity among existing studies are noted. Due to insufficient data and study limitations, additional preclinical and clinical trials are required to confirm these results and explore the therapy's long-term safety and efficacy. Graphical abstract Keywords: Intranasal administration, Stem cell derivative, Alzheimer's disease, Systematic review, Meta-analysis